The documents of Vatican II - Abbott, Walter M. (London, UK Geoffrey Chapman, 1967)
Contents : all sixteen official texts promulgated by the Ecumenical Council 1963-1965. Includes notes and commentas by Catholic, Protestant and Orthodox authorities. Includes index.
Keywords: Catholic church -- creeds -- history and criticism; Catholic church -- history -- 1965- -- sources